2013
DOI: 10.1177/1040638712473103
|View full text |Cite
|
Sign up to set email alerts
|

HoBi-like viruses

Abstract: The genus Pestivirus is composed of 4 important pathogens of livestock: Bovine viral diarrhea virus 1 and 2 (BVDV-1 and BVDV-2), Classical swine fever virus (CSFV), and Border disease virus of sheep (BDV). BVDV are major pathogens of cattle, and infection results in significant economic loss worldwide. A new putative pestivirus species, tentatively called “HoBi-like,” “BVDV-3,” or “atypical pestiviruses,” was first identified in Europe in fetal bovine serum (FBS) imported from Brazil. HoBi-like viruses are rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 35 publications
2
86
0
3
Order By: Relevance
“…Nevertheless, it is possible that the virus load isolated from nasal discharge samples on day 1 pi was a residue after the inoculation. BVDV infection can cause immunosuppression subsequent to viral replication in mononuclear cells; the latter also facilitates the occurrence of secondary respiratory and enteric infections (POTGIETER, 1995;BAUERMANN et al, 2013;FALkENBERG et al, 2014). In this study, WBCs decreased in all infected animals after day 3 pi, the largest reduction being observed on day 9 pi (20-37%), and cell counts almost returned to normal by day 15 pi.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Nevertheless, it is possible that the virus load isolated from nasal discharge samples on day 1 pi was a residue after the inoculation. BVDV infection can cause immunosuppression subsequent to viral replication in mononuclear cells; the latter also facilitates the occurrence of secondary respiratory and enteric infections (POTGIETER, 1995;BAUERMANN et al, 2013;FALkENBERG et al, 2014). In this study, WBCs decreased in all infected animals after day 3 pi, the largest reduction being observed on day 9 pi (20-37%), and cell counts almost returned to normal by day 15 pi.…”
Section: Discussionmentioning
confidence: 52%
“…Previous reports showed that exposure to BVDV may cause a subclinical infection or several clinical manifestations in cattle (BOTTON et al, 1998;BIANCHI et al, 2011). Previously, experimental inoculation of calves with field isolates has been used as a method to examine infection parameters under controlled conditions (BRUM et al, 2002;DECARO et al, 2012;BAUERMANN et al, 2013;RIDPATH et al, 2013); such analyses enable the characterization of many aspects of infection, such as its acute phase and pathogenesis, host immune response, the transmission between animals, and the efficacy of vaccine protection and diagnostic testing (BRUM et al, 2002;BAUERMANN et al, 2013). Several studies have been conducted using this protocol and the results of these studies showed that virulence is highly variable among strains (BRUM et al, 2002;DECARO et al, 2012;RIDPATH et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, HoBi-like viruses do not appear to be endemic on all continents. In South America, HoBi-like virus has been associated with reproductive disorders in Brazilian cattle herds and with the death of water buffalos (3,4,15). In Italy, the infection of cattle with HoBi-like virus resulted in abortion, respiratory disease, death of young animals, and the birth of PI calves (5,6,16).…”
mentioning
confidence: 99%
“…Infection with a putative pestivirus species, variously referred to as HoBi-like virus, BVDV3, and atypical pestivirus, leads to a repertoire of syndromes indistinguishable from that of BVD. Clinical signs include upper respiratory disease, fever, transient immune suppression, death among young stock, reproductive losses, and the generation of persistently infected (PI) animals (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%